Text Recycling in STEM Research: An Exploratory Investigation of Expert and Novice Beliefs and Attitudes. (July 2021) - Moskovitz, Cary; Hall, Susanne
When writing journal articles, science, technology, engineering and mathematics (STEM) researchers produce a number of other genres such as grant proposals and conference posters, and their new articles routinely build directly on their own prior work. As a result, STEM authors often reuse material from their completed documents in producing new documents. While this practice, known as text recycling (or self-plagiarism ), is a debated issue in publishing and research ethics, little is known about researchers' beliefs about what constitutes appropriate practice. This article presents results of from an exploratory, survey-based study on beliefs and attitudes toward text recycling among STEM "experts" (faculty researchers) and "novices" (graduate students and post docs). While expert and novice researchers are fairly consistent in distinguishing between text recycling and plagiarism, there is considerable disagreement about appropriate text recycling practice.